Incidence of article 2022 (enforceability of real property rights) of the civil code in the conflict between the unregistered right to property in good faith and the embargo in the form of registration in the legal proceedings of property third parties in - Franco Apaza, Pedro David (2020)
Objective: This research was conducted in order to determine the effect of Article 2022 (Enforceability of interests in land) of the Civil Code the right of property in good faith not registered and the embargo registration form in the Process Third party judicial of Property in Peru, 1996-200. Method: The research corresponds to the theoretical and applied type, with a nonexperimental descriptive explanatory design (ex post facto). The information was obtained with the application of the questionnaire, the Certificate of interview 27 and documentary analysis; used nominal scales and quantitative type. The study population is represented by lawyers, judges and judgments Casatorias issued by the Supreme Court. Results: In Peru Article 2022 (Enforceability of interests in land) of the Civil Code affects the conflict between the right of property in good faith not enrolled and yet in the form of registration in court proceedings of third party property in the Peru, 1996-200. The most important results are: a) Article 2022 of the Civil Code of Peru generates controversy in the valuation criteria applied by the Supreme judges when deciding on the mediation of property filed against embargoes in registration form; b) Article 2022 of the Civil Code does not guarantee legal certainty in judicial proceedings of third party property in Peru; c) There are deficiencies in the regulations prescribed in Article 2022 (Enforceability of Rights on Real Estate) of the Civil Code of Peru; and, d) Judicial Processes for third party property in Peru, must prioritize the embargo registration form. Conclusion: Article 2022 of the Civil Code of Peru generates controversy in the valuation criteria applied by the Supreme judges when deciding on the mediation of property filed against embargoes as enrollment, 1996-201